Inactivation of Escherichia coli in a baffled pond with attached growth: treating anaerobic effluent under the Sahelian climate. Issue 9 (2nd May 2016) - Moumouni, D.A.; Andrianisa, H.A.; Konaté, Y.; Ndiaye, A.; Maïga, A.H.
ABSTRACT: This study aimed to investigate and understand the zero-level detection of Escherichia coli ( E. coli ) at the outlet of an improved waste stabilization pond. Wastewaters were collected from the International Institute for Water and Environmental Engineering (2iE) campus and were subjected to biological treatment. The system included two-stage Anaerobic Reactors followed by a Baffled Pond (AR-BP) with recycled plastic media as a medium for attached growth and a control pond (CP). Three vertical baffles were installed, giving four compartments in the baffled pond (BP). The research was conducted on the pilot scale from March to July 2014, by monitoring E. coli, pH, temperature, dissolved oxygen (DO) and chlorophyll-a in each compartment and at different depths. The results show that E. coli concentrations were lower in top layers of all compartments with an undetectable level in the last compartment up to 0.60 m deep. E. coli mean removal efficiencies and decay rates were achieved by significant difference in BP (4.5 log-units, 9.1 day −1 ) and CP (1.1 log-units, 1.1 day −1 ). Higher values of pH (≥9), temperature (≥32°C), DO (≥ 8 mg/L) and chlorophyll-a (≥ 1000 µg/L) were observed at the surface of BP, whereas lower values were shown at the bottom. Sedimentation combined with the synergetic effects of the physicochemical parameters and environmental factors would be responsible for the inactivation of E. coli in BP. It was concluded that the AR-BP could be applied as an alternative low-cost wastewater treatment technology for developing countries and recommended for reuse of their effluent for restricted peri-urban irrigation.